2014
DOI: 10.1109/tim.2014.2318391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Measurements and Pseudomeasurements Correlation in Distribution System State Estimation

Abstract: Distribution system state estimation (DSSE) is one of the key elements of the monitoring activity of an active distribution network, and is the basis for every control and management application. The DSSE relies on real measurements collected by the distributed measurement system and on other available information, mainly obtained from historical data that help in obtaining observability. This prior information is necessary to derive the so called pseudomeasurements. Accurate input data are fundamental for an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 22 publications
0
55
0
10
Order By: Relevance
“…4) As demonstrated in [43], neglecting PMU correlations (both in amplitude and phase) in the estimator model does not lead to a significant decrease of the SE quality. 5) Voltage and current phasors are measured separately, per phase, i.e., we do not assume to use any 3-ph multifunction meter [44].…”
Section: A Linear Weighted Least Squares State Estimatormentioning
confidence: 91%
See 3 more Smart Citations
“…4) As demonstrated in [43], neglecting PMU correlations (both in amplitude and phase) in the estimator model does not lead to a significant decrease of the SE quality. 5) Voltage and current phasors are measured separately, per phase, i.e., we do not assume to use any 3-ph multifunction meter [44].…”
Section: A Linear Weighted Least Squares State Estimatormentioning
confidence: 91%
“…At this point, it is important to mention that, in principle, as analytically described in [43] and [44], R k can be a full matrix, since it is generally inappropriate to consider the measurement errors independent unless this hypothesis is properly justified. In our case, based on the observations that are mentioned in the following, we can neglect the correlations between different PMU measurements.…”
Section: A Linear Weighted Least Squares State Estimatormentioning
confidence: 99%
See 2 more Smart Citations
“…• measurement values obtained by different devices can be reasonably considered independent (e.g., [28]); • we only use PMUs, i.e., no typical measurements are used (e.g., power flows, power injections) or historical data; • voltage and current amplitude measurements taken by the same PMU can usually be considered uncorrelated [28]; • in [28] it is confirmed that neglecting PMU correlations (both in amplitude and phase) in the estimator model, does not lead to a significant decrease of the SE quality; • based on the nomenclature and definitions given in [29], we use only independent Gaussian-distributed measured data and not processed dependent measurements; • A unique sensor per measured quantity (i.e., voltage / current) is used and the cross-talk interference is negligible. In view of the above, R is diagonal and can be expressed as…”
Section: A Analysis Of Residualsmentioning
confidence: 99%